"A Banca do Serviço do Povo" Política e Economia durante o PREC (1974-75) - Noronha, Ricardo (Imprensa de História Contemporânea, 2018)
This book deals with the nationalization of the bank sector in the context of the Portuguese revolutionary process of 1974-75. Based on a vast collection of documentary sources and inspired by a set of theoretical tools developed by Mario Tronti, Walter Benjamin and Michel Foucault, it starts with an inescapable interrogation: how could a measure that was not included in the Armed Forces Movement Program and had such considerable implications, both in the short and in the long term, obtained enough support to be included in the Constitution as an irreversible conquest of the working class? The response developed in the following pages establishes an articulation between social conflicts and political economy, identifying it as the centre of gravity of the process that would lead to the nationalization of the bank sector. In this sense, it analyzes the way in which social struggles contributed to a process of cumulative radicalization, initiated at the end of the Estado Novo and which would gain increasing intensity throughout the revolutionary process. At the same time, it seeks to understand why the diagnosis of the economic situation contributed to polarize the political struggle, by mapping the lines of force of a debate that underwent successive declinations and covered different aspects, such as inflation, labour laws or property relations. In a context of economic and revolutionary crisis, the banking sector became a critical point in the capital-labour relation: credit concession would take on decisive importance after 25 April, with labour-unions accusing bankers of pursuing destabilization strategies associated with the practice of "economic sabotage"; in the wake of its nationalization, in turn, government officials, managers and trade-unionists sought to put "the banks at the service of the people", in the context of a brief experience of "socialist transition" that would make its way into the text of the Constitution. The case of the bank sector is therefore a privileged interpretative-key to identify the set of problems and the horizon of possibilities that dominated the historical conjuncture following the 25th of April. This book is a contribution to the maturation of the historiographical field dedicated to the interpretation of the revolutionary process of 1975-75, establishing a critical dialogue with the works that have been produced on the subject over the last years.